Plasma neutrophil gelatinase associated lipocalin diagnosed acute kidney injury in patients with systemic inflammatory disease and sepsis - Md Ralib, Azrina; Mat Nor, Mohd Basri; Pickering, John W. (Asian Pacific Society of Nephrology, 2017)
Aim: Sepsis is the leading cause of ICU admission. Plasma NGAL is a promising biomarker for AKI detection, however it is also increased with inflammation and few studies have been conducted in non-caucasion populations and/or in developing economies. Therefore, we evaluated plasma NGAL’s diagnostic performance in the presence of sepsis and systemic inflammatory response syndrome (SIRS) in a Malaysian ICU cohort. Methods: This is a prospective observational study on patients with SIRS. Plasma creatinine (pCr) and NGAL were measured on ICU admission. Patients were classified according to the occurrence of AKI and sepsis. Results: Of 225 patients recruited, 129 (57%) had sepsis of whom 67 (52%) also had AKI. 96 patients (43%) had non-infectious SIRS, of whom 36 (21%) also had AKI. NGAL concentrations were higher in AKI patients within both the sepsis and non-infectious SIRS cohorts (both p<0.0001). The diagnostic area under curve for AKI was 0.81 (95%CI: 0.74 to 0.87). The optimal cut-off was higher in sepsis compared to non-infectious SIRS patients (454 versus 176 ng/ml). Addition of NGAL to a clinical model comprising age, pCr, medical admission category and SAPS II score increased the mean risk of those with AKI by 4% and reduced the mean risk of those without AKI by 3%. Conclusions: AKI is more common with sepsis than non-infectious SIRS. Plasma NGAL was diagnostic of AKI in both subgroups. The optimal cut-off for diagnosing AKI was higher in sepsis Nephrology than in non-infectious SIRS. Addition of plasma NGAL improved the clinical model used to diagnose AKI